Evaluation of a Collagen-Reactive Monomer with Advanced Bonding Durability. (July 2020) - Yu, F.; Luo, M.L.; Xu, R.C.; Huang, L.; Zhou, W.; Li, J.; Tay, F.R.; Niu, L.N.; Chen, J.H.
This study evaluated the use of a new collagen-reactive monomer (CRM), isocyanate-terminated urethane methacrylate precursor, which has covalent affinity to dental collagen, in the formation of dentin-resin bonds and compared it with 2 other dental adhesives. Dentin specimens were bonded with either the CRM-based adhesive (CBA), One-Step (OS; Bisco, Inc.), or a negative adhesive (NA) control and subjected to 24-h storage in water, thermocycling to simulate 1-y clinical function, or a matrix metalloproteinase–mediated aging process. We tested the microtensile bond strength (µTBS), characterized the bonding interface with an atomic force microscope, conducted micro-Raman analysis, and performed leakage tests and in situ zymography. CBA and OS exhibited comparable bonding strength after 24 h ( P > 0.05); however, there was a sharp decrease in µTBS after aging for all except CBA ( P < 0.001). Raman spectra results indicated increased collagen crosslinking and chemical reaction between the adhesive and collagen in the CBA group. CBA achieved high-quality hybridization with collagen, improving mechanical properties and integrity, and decreased the enzyme-mediated degradation of the bonding interface by inhibiting collagenolytic activity. With the promising bonding durability of coapplied CBA, CRM may be the first dental adhesive to provide strong and long-lasting resin-dental collagen bonding without the additional conditioning step. The use of CBA results in high-quality hybrid layers that protect the resin-dentin interface from harmful biological and chemical activities commonly occurring in the oral environment.